Identifikasi Senyawa Mdma dan Paracetamol dalam Sampel Urine Menggunakan Metode Kromatografi Lapis Tipis dan Kromatografi Gas – Spektrofotometri Massa (Gc-Ms) - Ajeng Nita Aryani; Diva Rizqi Salsabilla; Putri Mutiara Iskandar; Silvana Lestari Irwansyah; Adella Aisiyah (Syntax Corporation Indonesia, 2022)
MDMA (3,4-methylenedioximet amphetamine) is a semisynthetic compound derived from stimulant type amphetamine (ATS) which works by triggering the release of serotonin. Paracetamol (acetaminophen) is one type of drug that has an analgesic-antipyretic effect. MDMA analysis requires a relatively fast method, so the TLC method was chosen. The identification test was carried out using 3 chromatographic systems, namely methanol: ammonia TA (100:1.5 v/v), methanol: butanol TAF (60:40 v/v), and Toluene: acetone: ethanol: ammonia TAEA (45: 45: 7: 3v/v/v/v). The determination test was carried out using the TAEA system and MDMA was used as a standard. The results of the identification test showed that the sample contained MDMA through the Hrfc and spectrum approaches. Qualitative Analysis of Paracetamol Compounds (Acetaminophen) in Urine aims to analyze paracetamol compounds (acetaminophen) in urine qualitatively by using gas chromatography - mass spectrometry (GC-MS). Extraction of paracetamol in urine samples was carried out using ethyl acetate, which was then derivatized using BSTFA containing 1% TMCS and analyzed using gas chromatography – mass spectrometry (GC-MS). The results showed that urine samples at 1, 2, and 3 hours after consuming paracetamol gave positive results for acetaminophen-TMS while at 24, 168, and 720 hours after consumption they were negative.